Perioperative Evolution of Sodium Levels in Cirrhotic Patients Undergoing Liver Transplantation: An Observational Cohort and Literature Review - Zamberg I (Dove Medical Press, 2021)
Ido Zamberg,1,2 Julien Maillard,1,* Benjamin Assouline,1,* Simon Tomala,1 Gleicy Keli-Barcelos,1 Florence Aldenkortt,1 Thomas Mavrakanas,2,3 Axel Andres,2,4 Eduardo Schiffer1,2 1Division of Anesthesiology, Department of Anesthesiology, Clinical Pharmacology, Intensive Care and Emergency Medicine, Geneva University Hospitals, Geneva, Switzerland; 2Faculty of Medicine University of Geneva, Geneva, Switzerland; 3Department of Medicine, McGill University Health Centre, Montreal, QC, Canada; 4Division of Transplantation, Department of Surgery, University Hospitals of Geneva, Geneva, Switzerland*These authors contributed equally to this workCorrespondence: Eduardo SchifferDivision of Anesthesiology, Department of Anesthesiology, Clinical Pharmacology, Intensive Care and Emergency Medicine, Geneva University Hospitals, Rue Gabrielle-Perret-Gentil 4, Geneva, CH-1205, SwitzerlandTel +41 22 372 30 60Fax +41 22 372 76 90Email eduardo.schiffer@hcuge.chBackground & Aims: Hyponatremia is an important predictor of early death among cirrhotic patients in the orthotopic liver transplantation (OLT) waiting list. Evidence exists that prioritizing OLT waiting list according to the MELD score combined with plasma sodium concentration might prevent pre transplantation death. However, the evolution of plasma sodium concentrations during the perioperative period of OLT is not well known. We aimed to describe the evolution of perioperative sodium concentration during OLT and its relation to perioperative neurohormonal responses.Methods: Twenty-seven consecutive cirrhotic patients who underwent OLT were prospectively included in the study over a period of 27 months. We studied the evolution of plasma sodium levels, the hemodynamics, the neurohormonal response and other biological markers during the perioperative period of OLT.Results: Among study’s population, four patients had hyponatremia before OLT, all with Child cirrhosis. In patients with hyponatremia, plasmatic sodium reached normal levels during surgery, and sodium levels remained within normal ranges 1 day, 7 days, as well as 6 months after surgery for all patients. Creatinine clearance was decreased significantly during the perioperative period, while creatinine and cystatin C levels increased significantly. Neutrophil gelatinase-associated lipocalin (NGAL) and vasopressin levels did not change significantly in this period. Plasma renin activity, concentrations of norepinephrine and brain natriuretic peptide varied significantly during the perioperative period.Conclusion: In our study, plasmatic sodium concentrations among hyponatremic cirrhotic patients undergoing OLT seem to reach normal levels after OLT and remain stable six months after surgery providing more evidence for the importance of sodium levels in prioritization of liver transplant candidates. Further investigation of rapid correction and stabilization of sodium levels after OLT, as observed in our study, would be of interest in order to fully understand the mechanisms involved in cirrhosis-related hyponatremia, its prognostic value and clinical implications.Keywords: liver, transplantation, hyponatremia, cirrhosis, MELD score